Ways to improve taxation of business entities in Uzbekistan - Karimov Mirolimjon Karimjon oʻgʻli (Genius Journals, 2025)
This article discusses the theoretical and practical issues of improving the taxation system of business entities in Uzbekistan. The ways of supporting entrepreneurial activity through liberalization of tax policy, simplification of taxation mechanisms and digitalization of tax administration are analyzed. Also, the existing problems in the taxation of small and medium-sized businesses, organizational and legal mechanisms for their elimination, and directions for improvement based on foreign experience are indicated. The results of the study include proposals aimed at creating a favorable tax environment for business entities, ensuring transparency of taxation, and stimulating economic growth
Keywords: taxation; business entity; tax policy; tax administration